GESTATIONAL TROPHOBLASTIC DISEASE - Rizal Sanif (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Gestational trophoblastic disease (GTD) is a group of tumors defined by abnormal trophoblastic proliferation. GTD is divided into hydatidiform moles (contain villi) and other trophoblastic neoplasms (lack villi).1 The malignant forms of the disease are also collectively known as gestational trophoblastic tumors or neoplasia (GTN).GTN includes the invasive mole, choriocarcinoma, placental site trophoblastic tumor, and epithelioid trophoblastic tumor. Southeast Asia and Japan have the highest reported incidence estimated to be two in 1000 pregnancies. In high-income countries, the incidence of a complete mole is approximately 1–3 per 1000 pregnancies, and the incidence of a partial mole is about 3 per 1000 pregnancies. Approximately 15–20% of patients will be treated for gestational trophoblastic neoplasia after the evacuation of complete hydatidiform mole. GTD develop from abnormal proliferation of trophoblastic tissue and form botryoid arranged vesicles. Risk factors include extremes of age, ethnicity, and a prior history of an HM, suggesting a genetic basis for its etiology. GTD causes a broad spectrum of different symptoms. The most frequent clinical symptom is abnormal vaginal bleeding. Other signs include uterine enlargement more significant than expected for gestational age, absent fetal heart tones, cystic ovary enlargement, hyperemesis gravidarum, and abnormally high level of β-hCG for gestational age. Ultrasound is the gold standard in non-invasive techniques, but histological examination is necessary to reach the final diagnosis. Different treatment modalities are available for gestational trophoblastic neoplasm depending on the type and stage; these include D&C (dilation and curettage), chemotherapy, hysterectomy, or a combination of these.2 The prognostic score for GTN reported by FIGO is a score of 0–6 is the low-risk group and 7 is the high-risk group. All patients who have hydatidiform mole should be up for β-hCG surveillance and monitoring. Most relapses occur within the first year after completion of chemotherapy. A generally approved schedule of β-hCG surveillance indicates monitoring weekly for six weeks after chemotherapy followed by biweekly measurements until six months after chemotherapy. Afterward, a biannual measurement of β-hCG for five years is sufficient.1 Seeing this, the determination of the diagnosis of GTD becomes very important. With the proper diagnosis, the management of the patient will also improve.